(untitled) - Jay H Krachmer (St. Louis, Missouri, 1995)
The book contains slide collections, ample experience in cornea and external eye disease, knowledge in photography and computer imaging. It provides a visual journey through ocular adnexal and anterior segment disease, with brief descriptions of important points along the way. Throughout this book, reference is made to the value of using various methods of slit lamp examination
Keywords: cornea - diseases - atlases,eye - diseases - atlases